Insert a joke about lawyers: Evaluating preferences for the Dark Triad traits in six occupations. (1st June 2020) - Kay, Cameron S.; Saucier, Gerard
Highlights: We examined perceptions of the Dark Triad traits in six occupations. Participants believed musicians and lawyers should be high in the Dark Triad. Participants believed teachers should be high in narcissism. Overall, participants believed others should have the same dark traits they have. Abstract: The current research examined how perceptions of the Dark Triad traits vary across occupations. Results from two studies ( N TOTAL = 933) suggested that participants believe it is acceptable, if not advantageous, for lawyers and musicians to be high in the Dark Triad traits. Participants, likewise, indicated that teachers should be high in narcissism but low in Machiavellianism and psychopathy. Potentially, the performative aspects of narcissism are considered an asset for teachers, while Machiavellianism and psychopathy are considered a liability. The findings further indicated that, regardless of the occupation in question, people high in a specific Dark Triad trait believe others should also be high in that same trait. All results are considered in the context of the attraction-selection-attrition model.